PH‐induced phase transition and crystallization of soft‐oxometalates (SOMs) into polyoxometalates (POMs): a study on crystallization from colloids. Issue 11 (16th October 2018) - Paul, Shounik; Sreejith, S. S.; Roy, Soumyajit
Abstract : Phase transition of colloidal TEA–MoO x SOM to crystalline K·β‐Mo8 POM depicting the pre‐existence of the SOM phase in the crystallization of POMs. Abstract : In this work, we demonstrate a simple approach for growing 1D (one‐dimensional) inorganic chains of K(C6 H16 N)3 Mo8 O26 ·H2 O polyoxometalates (POMs) from its colloidal soft‐oxometalate (SOM) phase through the variation of pH. The structure is composed mainly of a 1D inorganic chain with a β‐Mo8 O26 4− binding node linked using K + via Mo—O—K linkages, which results in a cuboctahedral geometry for the K + ions. Crystal structure and Hirshfeld surface studies reveal the role of triethylammonium cations in restricting the growth of the 1D chain into 2D/3D (two‐/three‐dimensional) structures. During the nucleation process from the heterogeneous SOM phase, some of the intermolecular interactions in the dispersion phase are retained in the crystal structure, which was evidenced from residual O…O interactions. The crystallization of the species from its colloidal form as a function of pH was studied by the use of Raman spectroscopy and it was found that the increase in volume fraction of the β‐Mo8 O26 4− species in the crystallizing colloidal mixture with the decrease in pH is responsible for the nucleation. This was monitored by time‐dependent DLS (dynamic light scattering) measurement and zeta‐potential studies, revealing the co‐existence of both the crystal and the colloidal forms at pH 3–2. This brings us to the conclusion that in the crystallization of POMs, the colloidal SOM phase precedes the crystalline POM phase which occurs via a phase transition. This work could open up avenues for the study of POM formation from the stand‐point of colloidal chemistry and SOMs.